2015
DOI: 10.1155/2015/293512
|View full text |Cite
|
Sign up to set email alerts
|

Decreased SplenicCD4+T-Lymphocytes in Apolipoprotein M Gene Deficient Mice

Abstract: Spleen T-lymphocytes, especially CD4+ T-cells, have been demonstrated to be involved in broad immunomodulation and host-defense activity in vivo. Apolipoprotein M gene (apoM) may have an important role in the regulation of immunoprocess and inflammation, which could be hypothesized to the apoM containing sphingosine-1-phosphate (S1P). In the present study we demonstrate that the splenic CD4+ T-lymphocytes were obviously decreased in the apoM gene deficient (apoM−/−) mice compared to the wild type (apoM+/+). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Special focus has been placed on the major subpopulation of the splenocytes (i.e., CD4 + T cells and CD8 + T cells. The immunological and functional aspects of T cells 10 d post-LPS treatment indicated T cell ensuing normal functionality (23,31). Indeed, the T cells' cytokine responses, upregulation of activation markers, or proliferation were previously found to be similar to the controls at this late, postacute time point in endotoxemia (23).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Special focus has been placed on the major subpopulation of the splenocytes (i.e., CD4 + T cells and CD8 + T cells. The immunological and functional aspects of T cells 10 d post-LPS treatment indicated T cell ensuing normal functionality (23,31). Indeed, the T cells' cytokine responses, upregulation of activation markers, or proliferation were previously found to be similar to the controls at this late, postacute time point in endotoxemia (23).…”
Section: Discussionmentioning
confidence: 87%
“…It was noticed that the mice suffered from lymphopenia because of systemic inflammation induced by LPS. Especially the T cell subpopulation CD4 + decreased compared with the CD8 + cell population upon LPS stimulation (23,31). The surviving mice regained their body weight, albeit not completely, and the clinical severity reduced after 5 d post-LPS treatment (23).…”
Section: Cd4 + and Cd8 + T Cell Analysismentioning
confidence: 99%
“…Elevated apoM levels were also reported in cases of chronic inflammatory disease and decreased in acute inflammatory disease [14, 15]. The potential mechanisms underlying the anti-inflammatory activities and immune-modulatory properties of apoM have been previously characterized [1618], and apoM is known to be widely distributed within the pool of serum lipoproteins under inflammatory conditions [19, 20]. In chronic inflammatory disease, apoM functions as an innate protective factor that is up-regulated to resist inflammatory effects over long periods.…”
Section: Discussionmentioning
confidence: 99%
“…Recently studies showed that apoM could limits endothelial and vascular inflammation though sphingosine 1-phosphate-sphingosine 1-phosphate receptor 1 pathway (S1P-SIP1) [21, 22]. Furthermore, Wang et al [18] showed that apoM contributed to the maintenance of CD4 + T lymphocytes or benefited for modifying T lymphocyte subgroups in murine spleen. Indeed, apoM-sphingosine 1-phosphate (apoM-S1P) was shown to contribute to innate and adaptive immunity by directly interacting with bone marrow lymphocyte progenitors and inhibiting their proliferation via activation of the S1P1/ERK pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…ApoM -/- mice (C57BL/6J) were employed at the animal research institute of the Nanjing University (Jiangsu) [ 29 ]. The genotypes of parental mice and their offsprings were analyzed by polymerase chain reaction as described previously [ 30 ].…”
Section: Methodsmentioning
confidence: 99%